(3JgPjH GddZIs - (3eMeO Hf CMeO Hf GdCRgQj GdgQhj, CHh efUhQ,J (B370 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH L a h i s
(3BNQgG (B:s
(3jfJgi HCKfGA HGH Gddaja ef MQa GdTjf T i s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B230s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B515s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs